Hubungan Tingkat Kecemasan dengan Kejadian Hipertenai pada Lansia di Puskesmas Kuta Alam Kota Banda Aceh - Mina Indrianti; Yusrika Yusrika; Mansuriza Mansuriza (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The prevalence of hypertension in the elderly continues to increase and is a major cause of morbidity and mortality. Uncontrolled blood pressure can lead to serious complications such as heart disease, stroke, and kidney failure. Anxiety, which is often experienced by the elderly, also plays a role in worsening hypertension through activation of the sympathetic nervous system and increased stress hormones. This study aims to determine the relationship between anxiety levels and the incidence of hypertension in the elderly at the Kuta Alam Community Health Center in Banda Aceh City. The study used a quantitative method with a cross-sectional analytical design. The study population consisted of 145 elderly people with hypertension, with a sample of 59 people selected through a purposive sampling technique. The study was conducted from April 28 to May 8, 2025. Anxiety levels were measured using the Geriatric Anxiety Inventory (GAI) questionnaire, and blood pressure was measured using a digital sphygmomanometer. Data analysis was carried out univariately and bivariately using the Chi-square test. The results showed that the majority of respondents experienced panic anxiety (39.0%) and Grade III hypertension (44.1%). There was a significant relationship between anxiety levels and the incidence of hypertension in the elderly (ρ = 0.000; ρ < 0.05). In conclusion, anxiety influences the severity of hypertension, so psychological aspects need to be considered in elderly health services at the Kuta Alam Community Health Center.